Advanced Blood-Brain Barrier Drug Delivery - Pardridge, William M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advanced Blood-Brain Barrier Drug Delivery is a reprint with a summary editorial, followed by 16 chapters that cover five areas of brain drug delivery, including receptor-mediated transport (RMT), carrier-mediated transport (CMT), active efflux transport (AET), Trojan horse lipid nanoparticles (LNP), and in vivo methods for measurement of drug transport across the blood-brain barrier (BBB).